2003
DOI: 10.1177/030802260306600407
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of the Canadian Model of Occupational Performance in a Forensic Rehabilitation Hostel

Abstract: In order to improve the quality and effectiveness of occupational therapy service provision, therapists should be using models of practice. This paper describes the Canadian Model of Occupational Performance and critically evaluates its application within a forensic rehabilitation hostel. It provides examples from practice and discusses the strengths and limitations of the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Chacksfield and Forshaw (1997) briefly mentioned the use of the Canadian Model of Occupational Performance (CMOP) (Canadian Association of Occupational Therapists [CAOT] 1993) in their occupational therapy programme on a forensic addictive behaviours unit at Broadmoor Hospital. Clarke (2003) provided a more thorough description of the application of the CMOP (CAOT 1997) in a secure hostel setting. Clarke (2003) listed the advantages of this model as being client-centred, having a focus on performance and the provision of assessment and evaluation tools, although these are not discussed in detail.…”
Section: Occupational Therapy Models Of Practice In a Forensic Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Chacksfield and Forshaw (1997) briefly mentioned the use of the Canadian Model of Occupational Performance (CMOP) (Canadian Association of Occupational Therapists [CAOT] 1993) in their occupational therapy programme on a forensic addictive behaviours unit at Broadmoor Hospital. Clarke (2003) provided a more thorough description of the application of the CMOP (CAOT 1997) in a secure hostel setting. Clarke (2003) listed the advantages of this model as being client-centred, having a focus on performance and the provision of assessment and evaluation tools, although these are not discussed in detail.…”
Section: Occupational Therapy Models Of Practice In a Forensic Settingmentioning
confidence: 99%
“…Clarke (2003) provided a more thorough description of the application of the CMOP (CAOT 1997) in a secure hostel setting. Clarke (2003) listed the advantages of this model as being client-centred, having a focus on performance and the provision of assessment and evaluation tools, although these are not discussed in detail. According to Clarke (2003), the application of the CMOP in the secure setting differed from that in a general psychiatric setting only in its consideration of the environment.…”
Section: Occupational Therapy Models Of Practice In a Forensic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In Canada, though the role and responsibilities of forensic occupational therapists were identified in the 1960s (Lloyd, ), research conducted within Canadian forensic mental health settings has been sparse (e.g. Clarke, ; Lin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have suggested that occupational therapy services in many criminal justice settings parallel occupational therapy practice in traditional mental health settings (Chacksfield, ; Clarke, ; Flood, ; O'Connell & Farnworth, ). In some ways, such comparisons are accurate.…”
mentioning
confidence: 99%